Relationship of parental social support with adolescent career planning - Rambe, Malim Soleh; Darwis, Muhammad; Siregar, Alfiansyah Halomoan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Adolescent career planning should ideally be given social support from parents, this support will help teenagers understand their talents and abilities, help teenagers obtain information about the career fields they are interested in, help teenagers to adapt the career fields they will plan to the teenagers' abilities and interests, so that it will make it easier for teenagers to determine career planning. In reality, there are still many teenagers who lack parental social support in their career planning efforts. The aim of this research is to describe the relationship between social support and adolescent career planning. This type of research is descriptive quantitative correlational. The research population was students in classes X and XI SMK Negeri 1 Padang registered in the 2022/2023 academic year with a total of 561 students and a sample of 237 students, taken using the stratified random sampling technique. Instrument used was a questionnaire prepared based on the Likert scale model. The research data were analyzed using percentage analysis and to test the research hypothesis the Pearson product moment correlation technique was used. The research results show that there is a significant relationship between parental social support and teenagers' career planning with a correlation coefficient of 0.500 at a significance level of 0.00 and the direction of the relationship is positive. The implication of this research is the need for maximum parental social support for teenagers, because this will make teenagers more precise in making career decisions. Then guidance and counseling teachers must improve various types of services that can support the development of teenagers' career decisions at school.